2020
DOI: 10.1002/dad2.12048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed prevalence of Alzheimer's disease and related dementias in Medicare Advantage plans

Abstract: Introduction One‐third of Medicare beneficiaries are enrolled in Medicare Advantage (MA). Yet, little is known about MA beneficiaries diagnosed with Alzheimer's disease (AD) and AD‐related dementias (AD/ADRD). Methods We calculated the prevalence of AD/ADRD diagnoses in 2014 and 2016 in three MA plans. We determined the demographic characteristics of beneficiaries diagnosed with AD/ADRD, and whether they disenrolled from the MA plan for any reason within 364 days from the index date. Results In 2014 and 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
6
19
1
Order By: Relevance
“…One‐year KPSC disenrollment rates are similar for members with (12%) and without (11%) ADRD, contrasting with aggregated nationwide MA plan data (2014–2015), where disenrollment rates for beneficiaries with an ADRD diagnosis were double those without (9.0% vs. 4.2%) and combined disenrollment and plan switching for both groups were much higher (28.7% in ADRD vs 27.0%) 17 than in KPSC. It is important to also note that the prevalence of ADRD (5.5%) in this health plan is comparable to published rates from other MA plans 18,19 …”
Section: Discussionsupporting
confidence: 78%
“…One‐year KPSC disenrollment rates are similar for members with (12%) and without (11%) ADRD, contrasting with aggregated nationwide MA plan data (2014–2015), where disenrollment rates for beneficiaries with an ADRD diagnosis were double those without (9.0% vs. 4.2%) and combined disenrollment and plan switching for both groups were much higher (28.7% in ADRD vs 27.0%) 17 than in KPSC. It is important to also note that the prevalence of ADRD (5.5%) in this health plan is comparable to published rates from other MA plans 18,19 …”
Section: Discussionsupporting
confidence: 78%
“…First, we are unable to validate the accuracy of diagnoses, including mental health diagnoses and dementia subtypes in Medicare claims data that may not include all new cases of dementia 43 . Second, our analyses did not include Medicare Advantage enrollees, who tend to be healthier with lower rates of ADRD 44–47 and more likely to initiate mental health care than fee‐for‐service Medicare enrollees even after adjusting for sociodemographic characteristics and mental and physical health 48 . Third, information was not available concerning clinical suicide risk factors such as lifetime history of self‐harm, 21 proximal stressful life events, 49 social disconnection (e.g., marital status, loneliness), 50 and access to lethal means.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sickest and most costly patients are more likely to disenroll from MA. [22][23][24][25] Using Medicare Beneficiary Survey data from 2010 to 2016, Park et al found only small differences in healthcare utilization of ADRD patients in MA compared to TM. 18 No study to date has examined MA and ACO care of persons with dementia, a high-cost and high-need population.…”
Section: Discussionmentioning
confidence: 99%